Recent Smoking History Is Not Associated with Adverse 30-Day Standardized Postoperative Outcomes following Microsurgical Reconstructive Procedures of the Upper Extremity. Issue 1 (February 2023) - Oleru, Olachi O.; Shah, Neil V.; Zhou, Peter L.; Sedaghatpour, Dillon; Mistry, Jaydev B.; Wham, Bradley C.; Kurtzman, Joey; Mithani, Suhail K.; Koehler, Steven M.
Background: Upper extremity (UE) microsurgical reconstruction relies upon proper wound healing for optimal outcomes. Cigarette smoking is associated with wound healing complications, yet conclusions vary regarding impact on microsurgical outcomes (replantation, revascularization, and free tissue transfer). We investigated how smoking impacted 30-day standardized postoperative outcomes following UE microsurgical reconstruction.Methods: Utilizing the National Surgical Quality Improvement Program, all patients who underwent (1) UE free flap transfer (n = 70) and (2) replantation/revascularization (n = 270) were identified. For each procedure, patients were stratified by recent smoking history (current smoker ≤1-year preoperatively). Baseline demographics and standardized 30-day complications, reoperations, and readmissions were compared between smokers and nonsmokers.Results: Replantation/revascularization patients had no differences in sex, race, or body mass index between smokers (n = 77) and nonsmokers. Smokers had a higher prevalence of congestive heart failure (5.2% vs 1.0%, P = .036) and nonsmokers were more often on hemodialysis (15.6% vs 10.4%, P = .030). Free flap transfer patients had no differences in age, sex, or race between smokers (n = 14) and nonsmokers. Smokers had a longer length of stay (6.6 vs 4.2 days, P = .001) and a greater prevalence of chronic obstructive pulmonary disorder (COPD; 7.1% vs 0%, P = .044). Recent smoking was not associated with increased odds of any 30-day minor and major standardized surgical complications, readmissions, or reoperations following UE microsurgical reconstruction via free flap transfer or replantation/revascularization. Baseline diagnosis of COPD was also not a predictor of adverse 30-day outcomes following free flap transfer.Conclusion: Recent smoking history was not associated with any 30-day adverse outcomes following UE microsurgical reconstruction via replantation/revascularization or free flap transfer. In light of these findings, further investigation is warranted, with particular focus on adverse events specific to free flaps and replantation/revascularization.